Antitumor Effects of Natural Compounds Derived from Allium sativum on Neuroblastoma: An Overview - Carlos César Patiño-Morales; Ricardo Jaime-Cruz; Concepción Sánchez-Gómez; Juan Carlos Corona; Estefani Yaquelin Hernández-Cruz; Ivia Kalinova-Jelezova; José Pedraza-Chaverri; Perla D. Maldonado; Carlos Alfredo Silva-Islas; Marcela Salazar-García (MDPI AG, 2021)
Garlic (Allium sativum) has been used in alternative medicine to treat several diseases, such as cardiovascular and neurodegenerative diseases, cancer, and hepatic diseases. Several publications have highlighted other features of garlic, including its antibacterial, antioxidative, antihypertensive, and antithrombotic properties. The properties of garlic result from the combination of natural compounds that act synergistically and cause different effects. Some garlic-derived compounds have been studied for the treatment of several types of cancer; however, reports on the effects of garlic on neuroblastoma are scarce. Neuroblastoma is a prevalent childhood tumor for which the search for therapeutic alternatives to improve treatment without affecting the patients' quality of life continues. Garlic-derived compounds hold potential for the treatment of this type of cancer. A review of articles published to date on some garlic compounds and their effect on neuroblastoma was undertaken to comprehend the possible therapeutic role of these compounds. This review aimed to analyze the impact of some garlic compounds on cells derived from neuroblastoma.